2021
DOI: 10.31557/apjcp.2021.22.7.2221
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis for Association of XRCC1, XRCC2 and XRCC3 Polymorphisms with Susceptibility to Thyroid Cancer

Abstract: Background:We conducted a comprehensive meta-analysis to explore the association of polymorphisms at XRCC1, XRCC2 and XRCC3 genes with susceptibility to thyroid cancer (TC). Methods: We searched PubMed, EMBASE, Web of Science, and CNKI for relevant available studies. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of the associations. Results: A total of 67 studies including 17 studies with 6,806 cases and 5,229 controls on XRCC1 Arg399Gln, 13 studies with 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The X-ray repair cross-complementing 2 (XRCC2) gene, located at 7q36.1, is a member of the RecA/Rad51related protein family that participates in homologous recombination repair (HRR) to maintain chromosome stability and repair DNA damage [13,[20][21][22][23]. Thus, XRCC2 is a functional candidate for involvement in cancer progression [24][25][26].…”
Section: Reviewmentioning
confidence: 99%
“…The X-ray repair cross-complementing 2 (XRCC2) gene, located at 7q36.1, is a member of the RecA/Rad51related protein family that participates in homologous recombination repair (HRR) to maintain chromosome stability and repair DNA damage [13,[20][21][22][23]. Thus, XRCC2 is a functional candidate for involvement in cancer progression [24][25][26].…”
Section: Reviewmentioning
confidence: 99%
“…The results of several meta-analyses yielded conflicting results, suggesting the complexity of the association between XRCC1 polymorphisms and thyroid cancer risk depending on ethnicity. Mandegari et al conducted a meta-analysis on polymorphisms in the XRCC1 gene—rs25487, rs25489, and rs1799782—and did not demonstrate a significant association with the risk of thyroid cancer [ 38 ]. However, subgroup analysis suggested an association of rs25487 with the risk of thyroid cancer in Caucasians but not in the Asian population.…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%
“…However, a polygenic risk analysis, taking into account genotype combinations of different DNA repair genes, including RAD52 (CC)/ XRCC2 (GG)/ XRCC3 (CT + TT) (OR = 2.204; 95% CI = 1.08–4.51; p = 0.029), have indicated positive association where the combined variant RAD52 / XRCC2 / XRCC3 showed a significant five-fold increase in the risk of thyroid cancer compared to the wild type (OR = 5.04; 95% CI = 1.45–17.58; p = 0.007) [ 43 ]. However, the overall and combined meta-analyses showed that the XRCC2 rs3218536 polymorphism was not significantly associated with the risk of thyroid cancer [ 38 , 45 ]. The genotypic frequencies of selected SNPs of the XRCC2 gene in various populations and their associations with the risk of thyroid cancer are presented in Table 2 .…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%
See 1 more Smart Citation